ULTRA HD-VIDEOINFORMATION COMPRESSION IN DISTRIBUTED COMPUTER SYSTEM - Skrupsky, S. Y. (Radio Electronics, Computer Science, Control, 2013)
The article deals with the parallelization of Ultra HD-videoinformation compression process in distributed system. The advantages and disadvantages of modern Ultra HD video format have been discussed. The evaluation of the computational complexity of the motion estimation operation in video sequences has been performed. The method for video distribution over the nodes of a distributed system, based on correlation analysis of video frames with the dynamic sensitivity function, has been analyzed. It has been used for parallelization of videoinformation compression process at Pukhov Institute for Modelling in Energy Engineering cluster. The objective indicators of Ultra HD-videoinformation compression results in a distributed system depending on used motion estimation algorithm and the width of the motion vectors search region have been investigated experimentally. The overheads of videoinformation compression process in distributed system have been analyzed.